Reinventing the supply chain life cycle : student workbook - Schniederjans, Marc J. (FT Press, 2012)
With this up-to-date, hands-on study guide to accompany the innovative reference on managing the supply chain lifecycle, authors Schniederjans and Legrand help students and practitioners master all aspects of recasting and improving the global supply chain, and prepare them for professional certification as well as advanced degrees on the topic. Fully aligned with the current edition of Reinventing the Supply Chain Lifecycle , this workbook-style book includes chapter learning objectives, chapter summaries, chapter questions, reviews of key terms and concepts, additional cases and examples, student self quizzes, and more.